Knowledge and awareness of osteoporosis and its related risk factors among the undergraduate students of doctor of physical therapy in Karachi, Pakistan - Tariq, Varisha; Khalid Khan, Zainab; Paracha, Hafsa (International Journal of Endorsing Health Science Research, 2018)
Background: Osteoporosis (OP) is a chronic progressive skeletal muscle disorder, which leads to an increased risk of fracture due to low mineral density. It is one of the major global health problems and most people are unaware of it. Education of OP was one of the key factors to reduce the risk from the society. Methodology: This observational cross-sectional survey was conducted from October 2017 to March 2018. A sample size of 252 was calculated through Open Source Epidemiologic Statistics for Public Health (Open EPI) version 3.0 with a hypothesized frequency of 79.4% confident limit of 5%, design effect of 1% and confidence level of 95%. Undergraduate students of DPT i.e. 3rd to 5th-year students were research participants & those who already had some knowledge regarding OP via any kind of workshop and conference were excluded. Non-probability purposive sampling technique was used for sampling purpose. OP was evaluated through OKAT scale. Statistical Package of Social Sciences (SPSS) version 20 was selected for data entry and analysis. Result: Out of 252 participants, 81.3% of students were female while only 18.7% were males. According to our results, 20.6% students were found having poor knowledge regarding OP, 77% participants had satisfactory knowledge and only 2.4% students were having good knowledge regarding the awareness of OP and its related risk factors. Conclusion: OP is a crucial health problem which is significantly rising in many countries, so the awareness regarding this progressive disorder is essential. Interventional programmes and campaigns should be held across the globe to increase awareness in society.